The influence of leadership style, work motivation, work discipline on employee performance at Perumda Pasar Jaya Central Jakarta - Ilham Nur Muhammad; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study was conducted in order to analyze the Influence of Leadership Style, Work Motivation, and Work Discipline on Employee Performance at Perumda Pasar Jaya Central Jakarta. The sample in this study was 120 respondents based on the Yamane formula. The data used in this study came from primary data assisted by questionnaires that had been distributed to 120 respondents. Related to data analysis, this study uses inferential analysis with multiple linear regression. It is known that the results obtained in this study are that Leadership Style has a good impact on employee performance, work motivation has a good impact on employee performance, and work discipline has a good impact on employee performance. Therefore, Perumda Pasar Jaya Central Jakarta should have a better impact so that it can continue to maintain stability